2019
DOI: 10.1186/s41610-019-0129-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plant on distribution of an endangered butterfly, Leptalina unicolor (Bremer & Grey, 1853), in restored riverside areas along the Geum River

Abstract: Background: The dramatic worldwide decline in the butterfly species Leptalina unicolor (Bremer & Grey) is largely the result of continuous habitat decline and disturbance by humans. The discovery of a narrow habitat in riverside wetlands utilized by L. unicolor raises the hope that such restricted key areas could be rather easily protected. Results: Here, we explain the environmental variables and habitat characteristics that primarily influence the distribution of L. unicolor discovered at the riverside areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In South Korea, small populations have been identified in areas, such as Miryang‐si (Jeyak Mountain), Inje‐gun (Simjeok Wetland), and Buyeo‐gun (Geum River) (Choi et al . 2019). It is recognized as an endangered species according to the Korean Red List of Threatened Species (NIBR 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In South Korea, small populations have been identified in areas, such as Miryang‐si (Jeyak Mountain), Inje‐gun (Simjeok Wetland), and Buyeo‐gun (Geum River) (Choi et al . 2019). It is recognized as an endangered species according to the Korean Red List of Threatened Species (NIBR 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that 13 plant species, including Salix koreensis , Lespedeza cuneata , Paspalum distichum , and Festuca arundinacea , host L. unicolor (Choi et al . 2019). However, M. sinensis is the principal host of this butterfly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations